Crucial Involvement of IL-6 in Thrombus Resolution in Mice via Macrophage Recruitment and the Induction of Proteolytic Enzymes - Nosaka, Mizuho; Ishida, Yuko; Kimura, Akihiko; Kuninaka, Yumi; Taruya, Akira; Ozaki, Mitsunori; Tanaka, Atushi; Mukaida, Naofumi; Kondo, Toshikazu (Frontiers in Immunology, 2020)
After the ligation of the inferior vena cava (IVC) of wild-type (WT) mice, venous thrombi formed and grew progressively until 5 days, and resolved thereafter. Concomitantly, intrathrombotic gene expression of Il6 was enhanced later than 5 days after IVC ligation. IL-6 protein expression was detected mainly in F4/80-positive macrophages in thrombus. When Il6-deficient (Il6-/-) mice were treated in the same manner, thrombus mass was significantly larger compared with WT mice. Moreover, the recovery of thrombosed IVC blood flow was markedly delayed in Il6-/- compared with WT mice. F4/80-positive macrophages in thrombus expressed proteolytic enzymes such as matrix metalloproteinase (Mmp)2, Mmp9 and urokinase-type plasminogen activator (Plau) and their mRNA expression was significantly reduced in Il6-/- mice. Consistently, the administration of anti-IL-6 antibody delayed the thrombus resolution in WT mice while IL-6 administration accelerated thrombus resolution in WT and Il6-/- mice. Moreover, IL-6 in vitro enhanced Mmp2, Mmp9 and Plau mRNA expression in WT-derived peritoneal macrophages, in a dose-dependent manner and the enhancement was abrogated by a specific Stat3 inhibitor, Stattic. Thus, IL-6/Stat3 signaling pathway can promote thrombus resolution by enhancing Mmp2, Mmp9 and Plau expression in macrophages.